2014
DOI: 10.1038/bjc.2014.479
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of low- and high-grade cervical abnormalities associated with high uptake of the HPV bivalent vaccine in Scotland

Abstract: Background:In Scotland, a national HPV immunisation programme began in 2008 for 12- to 13-year olds, with a catch-up campaign from 2008 to 2011 for those under the age of 18. To monitor the impact of HPV immunisation on cervical disease at the population level, a programme of national surveillance was established.Methods:We analysed colposcopy data from a cohort of women born between 1988 and 1992 who entered the Scottish Cervical Screening Programme (SCSP) and were aged 20–21 in 2008–2012.Results:By linking d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
137
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(146 citation statements)
references
References 21 publications
8
137
0
1
Order By: Relevance
“…Similarly, a report in Denmark (Baldur-Felskov et al 2014) on uterine cervical cancer screening for women aged 20-21 years showed that atypical cells, CIN2 and CIN3 decreased by about 60%, 73%, and 80%, respectively. A study in Scotland (Pollock et al 2014) also showed that CIN3 decreased by about 55% after vaccination. Our data are essentially similar to the findings in Australia, Demark and Scotland.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, a report in Denmark (Baldur-Felskov et al 2014) on uterine cervical cancer screening for women aged 20-21 years showed that atypical cells, CIN2 and CIN3 decreased by about 60%, 73%, and 80%, respectively. A study in Scotland (Pollock et al 2014) also showed that CIN3 decreased by about 55% after vaccination. Our data are essentially similar to the findings in Australia, Demark and Scotland.…”
Section: Discussionmentioning
confidence: 92%
“…6,8 Statistics Canada provided neighbourhood income quintiles based on dissemination area, which was further linked to postal code. Rural residency designation was created by Alberta Health, based on population densities and travel times to a variety of health services.…”
Section: Covariatesmentioning
confidence: 99%
“…3,4 Vaccination against HPV should reduce the prevalence of cervical dysplasia; thus, screening outcomes provide early evidence of the effectiveness of HPV vaccination against cancer. [5][6][7][8] Data are lacking on the association between Pap test results and HPV vaccination in the North American context. [9][10][11] The province of Alberta has a population-based program for cervical cancer screening and HPV vaccination, and is well positioned to address this knowledge gap.…”
mentioning
confidence: 99%
“…HPV vaccination prevents infection with HPV 16 and 18 [2][3][4] and is associated with a reduction in all grades of histological and cytological abnormalities according to data from population-based immunisation programmes 5,6 . The bivalent vaccine also provides immunological cross-protection against HPV 31, 33 and 45, high-risk oncogenic HPV types phylogenetically related to HPV 16 and 18, although the duration and scale of long-term crossprotective immunity has been vigorously debated 3,[7][8][9] .…”
Section: Introductionmentioning
confidence: 99%